The Internalization of Tolerance Values through Multicultural-Based Islamic Religious Education in Public Schools - Purlina Purlina; Baili Baili; Siti Khamim; Ulfa Adilla; Mabruri Mabruri (The Future of Education Journal, 2024)
This study aims to analyze the process of internalizing tolerance values through multicultural Islamic Religious Education (IRE) in public schools. Employing a qualitative approach with a multi-site case study design, the research was conducted in three public senior high schools located in urban and semi-urban areas. Data were collected through participant observation (12 classroom sessions in each school), in-depth interviews with IRE teachers and students, and analysis of instructional documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the internalization of tolerance values was achieved through three main strategies: (1) the integration of multicultural content into moral education and social jurisprudence (fiqh al-mu‘āmalah) materials; (2) collaborative project-based learning involving interfaith and intercultural engagement; and (3) reflective habituation through spiritual journals and ethical discussions. Supporting factors included teachers’ pedagogical competence, supportive school policies, and an inclusive social climate. The primary challenges were limited instructional time, resistance stemming from narrow textual interpretations, and insufficient teacher training in multicultural educational approaches. This study contributes theoretically to the development of contextual Islamic Religious Education models and provides practical guidance for implementing tolerance education in public schools. It is recommended that teachers’ capacities be strengthened through continuous professional development programs and that tolerance-related attitude assessments be integrated into the Merdeka Curriculum framework.